Analisis Risiko Kegagalan Komponen Water Tube Boiler Menggunakan Metode Failure Mode and Effect Analysis pada Industri Pengolahan Minyak Kelapa Sawit - Tomi Tampubolon; Akmal Indra; Agnes Arum Budiana (Jurnal Ragam Pengabdian, 2026)
A water tube boiler is a critical utility unit in the palm oil processing industry because it supplies steam for power generation and production processes. Component failures in boiler systems may cause production downtime, efficiency losses, and increased maintenance costs. This study aims to analyze the risk level of water tube boiler component failures using the Failure Mode and Effects Analysis method. The research was conducted on two water tube boiler units in a palm oil processing industry using historical maintenance data from January to December 2024. The analysis was performed by identifying failure modes, assigning severity, occurrence, and detection scores, and calculating the Risk Priority Number for each failure mode. The results showed that the highest risk in Boiler 1 was economizer tube leakage with an RPN value of 360. Meanwhile, the highest risk in Boiler 2 was ID Fan ducting failure with an RPN value of 450. The average RPN values for Boiler 1 and Boiler 2 were 233.48 and 242.63, respectively. These findings indicate that maintenance priorities should focus on the economizer, ID Fan, feed water pump, and conveyor system. This study provides a risk-based basis for determining critical components and improving boiler maintenance planning.